The first Philippine species of Marcepania (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
The genus Marcepania is a sole member of the tribe Marcepaniini, known to occur in SE Asia. The five hitherto described species inhabit the Malay Peninsula and Borneo. The first species discovered in the Philippines, Marcepania princesa sp. n. is described here, based on a male specimen found on the island of Palawan. It is most similar to its geographically closest relative, M. elongata of northern Borneo.